Economic growth and universities: enpirical evidence for Mexico - Kido Cruz, Antonio; Luna Campos, Felipe Andoni (2021)
The research is a descriptive analysis of economic growth in Mexico (EGM) and the evolution of two variables, which are the number of colleges and universities (NU) and the rate of growth of colleges and universities (GRU). The results suggest that differences in the averages of the variable EGM in at least two groups of the categorical variable GRU. The model estimates from panel data indicate that a 100% increase in the number of public universities is positively and significantly related with a growth of 38.2% in the GDP per capita in the states of Mexico.